Play or pay to win: a World of Warcraft case study - Papaefstathiou, Savvas (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2020)
The current research focuses on the video game World of Warcraft and tries to examine the terms of “Ludocapitalism”, “Playbour” and the very idea of “Magic Circle” within the game. Since the start of the game until 15 years later people invented ways to make their gaming experience easier or more rewarding. It started with goldfarming were people would farm in-game gold and then sell it for real life money until today where people created communities and enterprises were they not getting only real life money but also gold currency as reward. A whole new economic model is now in the making, not only in World of Warcraft but in many games. Through this research an effort is made to understand how players understand and react to these boosting services and the new economic system but also examine the concept of commercialization in video games. The research collected the data by interviewing players of the game but also going through communities’ servers and websites. After the end of the procedure, the researcher transcribed all the recordings for an extensive and thorough thematic analysis. Inductive and Semantic approaches were used for a deeper understanding of the transcripts. Highlights of the findings were the structure of the communities that now look like enterprises and the new era of online digital games. Now games look more like work opportunities rather a place to have fun and play. Playbour and loudocapitalism is implemented and the commercialization is promoted through World of Warcraft. Even if players are not familiar with more academic terminologies, they are quite aware of the playbour inducted in digital games that are now much alike a workplace. It is important to distinguish play and work and don’t mask each other for more revenue and profit. Least but not last, the following question emerged from the research: “ If only within an online multiplayer game so much income can flourish, then we can as well wonder how people that don’t have an idea of how to run a company, can manage to run such services within a game. But also, how that situation impacts the society and the balance between leisure and working.”
Keywords: Playbour; Pay to Win; Loudocapitalism; Digital Games